Perbedaan Kadar Protein dan Kadar Lemak Ikan Patin (Pangasius hypophtalmus) yang Diolah secara Digoreng, Dipanggang dan Direbus - Nany Suryani; Rosita Rosita; Uswatun Hasanah; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Catfish (Pangasius hypophtalmus) is a high source of protein, but it also contains unsaturated fatty acids, and various vitamins and minerals that the body needs. However, the processing can lower nutrient content, including the protein and fat contents. This research aims to analyzing differences of protein and fat contents of catfish (Pangasius hypophtalmus) are processed in fried, grilled and boiled. This research is a quantitative research design completely randomized design with 4 treatments, 1 control and 3 treatments. Testing for protein content using the Kjeldahl method and to test the fat content using the Soxhlet. Statistical analysis using One way ANOVA. Based on statistical analysis found there are difference in protein levels p = 0.004 and fat levels p = 0,000 in catfish (Pangasius hypophtalmus) are processed in fried, grilled and boiled. To obtain the levels of protein and fat content, it can be selected either by boiling cooking techniques.